1999
DOI: 10.1093/glycob/9.11.1181
|View full text |Cite
|
Sign up to set email alerts
|

Secreted human conjunctival mucus contains MUC5AC glycoforms

Abstract: This study addresses the extent of variation in secreted end-product mucins in human conjunctival mucus. The aim was to determine whether the variety of mucin species found was encompassed by the mucin genes which have been cloned to date. Extraction into guanidine hydrochloride and separation of mucin constituents, by a combination of cesium chloride density gradient centrifugation, size separation on Sepharose CL-2B, MonoQ ion exchange chromatography and agarose gel electrophoresis, demonstrates a complex mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…After a minimum of 24 h dispersal in the chaotrope, mucins were purified from the samples using methods as previously described, for dog, rabbit [32] and human samples [33]. Briefly, mucins were isolated from proteins, glycoproteins, and nucleic acids by caesium chloride density gradient centrifugation at a starting density of 1.4 g/ml, Fractions were pooled between 1.3 and 1.47 g/ml, and subjected to gel filtration on Sepharose CL-4B columns.…”
Section: Collection Of Mucus Samples and Purification Of Mucinsmentioning
confidence: 99%
“…After a minimum of 24 h dispersal in the chaotrope, mucins were purified from the samples using methods as previously described, for dog, rabbit [32] and human samples [33]. Briefly, mucins were isolated from proteins, glycoproteins, and nucleic acids by caesium chloride density gradient centrifugation at a starting density of 1.4 g/ml, Fractions were pooled between 1.3 and 1.47 g/ml, and subjected to gel filtration on Sepharose CL-4B columns.…”
Section: Collection Of Mucus Samples and Purification Of Mucinsmentioning
confidence: 99%
“…Mucins are decorated with epitopes whose ligands can be found on cells of the immune system (Hajela et al 1994;Handa et al 1997;Kim et al 1999;Prakobphol et al 1999;Leppanen et al 2002). We have shown that these epitopes are also common on normal human ocular mucins (Berry et al 1996(Berry et al , 2000(Berry et al , 2003Ellingham et al 1999).…”
Section: Introductionmentioning
confidence: 98%
“…It is constituted primarily of secretory MUC5AC mucin secreted from conjunctival goblet cells (28), while membrane-bound mucins, MUC1 and MUC4, are present on corneal and conjunctival epithelial cells (1), with recent evidence that a soluble form of MUC4 is present in human tears (41). Ocular mucin is polydisperse, consisting of species with different size, charge, and glycosylation patterns (3,17,23) that contribute to the structure and function of mucus.…”
mentioning
confidence: 99%